1998
DOI: 10.1021/ma961549e
|View full text |Cite
|
Sign up to set email alerts
|

Isothermal Growth and Reorganization upon Heating of a Single Poly(aryl−ether−ether−ketone) (PEEK) Spherulite, As Imaged by Atomic Force Microscopy

Abstract: We have studied by atomic force microscopy (AFM, topographical imaging) the evolution of a single PEEK spherulite in a thin film during isothermal cold-crystallization and upon subsequent reheating to increasingly higher temperatures. To open the spherulitic microstructure, we added 30% w/w of an amorphous diluent (poly(ether−imide), PEI) serving as a marker. Small-angle X-ray scattering and dynamic mechanical analysis were used to check on bulk samples that similar structural evolutions are obtained when rehe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
28
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 34 publications
0
28
0
Order By: Relevance
“…It is also observed that nodules develop to lath-like lamellae through merging or lateral aggregation [11,12]. At larger scale, the sheaf-like structures can be observed [14], and category 2 spherulites [6] are developed [15]. Crystal structures developed from the glassy state thus show distinct features from those developed from solution.…”
Section: Introductionmentioning
confidence: 98%
“…It is also observed that nodules develop to lath-like lamellae through merging or lateral aggregation [11,12]. At larger scale, the sheaf-like structures can be observed [14], and category 2 spherulites [6] are developed [15]. Crystal structures developed from the glassy state thus show distinct features from those developed from solution.…”
Section: Introductionmentioning
confidence: 98%
“…Recent advances in techniques of atomic-force microscopy (AFM) have added significant convenience in probing the surface topography, lamellar, and crystal structures in banded rings in various polymer spherulites. [15][16][17][18][19] There are still largely unresolved debates on origins or mechanism of ring-band patterns in polymer spherulite; however, there have been no attempts to evaluate and compare the thermal behavior of ring-band versus Maltesecross spherulites. Regardless of crystallization temperature, PEA possesses only a single type of crystal cell, i.e., no polymorphism in PEA; however, it can exhibit ring spherulites as well as typical Maltese-cross ones.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, atomic force microscopy (AFM) has been utilized to study the organization of spherulites and the crystallization process of polymers. 10,11 A copolymer, poly(bisphenol A-co-octane), 12 was synthesized with the following structure:…”
mentioning
confidence: 99%